High way engineering - Oglesby, Clarkson; Hicks, R. Gary (New York : John Wiley & Son, Inc., 1982)
The major focus of this work is on transporting people and goods by highway. The planning, financing, legal requirements, design, construction, operation, and maintenance of facilities and their economic, social, and environmental consequences are thoroughly discussed.
1. Introduction -- 2. Highway and Urban Transportation Systems, Organizations, and association -- 3. Highway and Urban transportation -- 4. Economy and resource use -- 5. Financing highways and public transportation -- 6. Computations, Surveys and plans -- 7. Legal problems in transportation -- 8. Driver, Vehicle traffic and road characteristics -- 9. Highway design -- 10. Highway Operations- Traffic Engineering -- 11. Drainage -- 12. Highway Accident Prevention -- 13. Transportation and the Environment -- 14. Soils and materials -- 15. Constructing the roadbed -- 16. Gravel and crushed rock roads- stabilized roads -- 17. Base Courses -- 18. Macadam Surfaces -- Macadam bases -- 19. Bituminous Pavements -- 20. Portland cement-concrete pavements -- 21. Highway Maintenance and Rehabilitation.
Includes bibliographical references and index.
Keywords: HIGHWAY ENGINEERING